Official Angry Birds: Side-Splitting, Rib-Tickling Joke Book (Britain Egmont, 2012)
A double-sided joke book packed with gags. One side stars the ever-conquering birds, then flip over to read more from their arch-nemesis - the pigs!
Include Illustration
Keywords: Wit and humor, Juvenile -- Angry Birds (Game)